Effect of Head Position on Intraocular Pressure During Lumbar Spine Fusion: A Randomized, Prospective Study. (18th November 2015) - Emery, Sanford E.; Daffner, Scott D.; France, John C.; Ellison, Matthew; Grose, Brian W.; Hobbs, Gerald R.; Clovis, Nina B.
Abstract : Background: Ischemic optic neuropathy resulting in visual loss is a rare but devastating complication of spine surgery. Elevated intraocular pressure (IOP) results in decreased perfusion and possibly ischemic optic neuropathy. We performed a randomized, prospective trial to evaluate the effect of head positioning on IOP during lumbar spine fusion. Methods: The study included fifty-two patients treated at one institution. Inclusion criteria were a lumbar spine fusion and an age of eighteen to eighty years. Exclusion criteria were a diagnosis of tumor, infection, or traumatic injury or a history of eye disease, ocular surgery, cervical spine surgery, chronic neck pain, or cervical stenosis. The control group underwent the surgery with the head in neutral and the face parallel to the level operating room table whereas, in the experimental group, the neck was extended so that the face had a 10° angle of inclination in relation to the table. IOP measurements were recorded along with the corresponding blood pressure and PCO2 values at the same time points. The primary outcome measure was the change in intraocular pressure (ΔIOP, defined as the maximum IOP minus the initial IOP). Results: Analysis of covariance (ANCOVA) was used for categorical risk factors, and regression analysis was used for continuous risk factors. The mean ΔIOP, corrected for duration of surgery, was significantly (p = 0.0074) lower in the group treated with the head elevated than it was in the group treated with the head in neutral (difference between the two groups, 4.53 mm Hg [95% confidence interval, 1.29 to 7.79 mm Hg]). No patient sustained visual loss or any cervical-spine-related complications. Conclusions: Head elevation for adult lumbar spine fusion performed with the patient prone resulted in significantly lower IOP measurements than those seen when the operation was done with the patient's head in neutral. As lower IOP correlates with increased optic nerve perfusion, this intervention could mitigate the risk of perioperative blindness after spine surgery done with the patient prone. Level of Evidence: TherapeuticLevel I . See Instructions for Authors for a complete description of levels of evidence.